Cloning, sequencing and extracellular expression of the alkaline protease gene from Bacillus stearothermophilus F1 - Fu, Zhibiao (2001)
The gene of a highly thermostable alkaline protease was amplified from Bacillus stearothermophilus F1 by polymerase chain reaction using consensus primers based on the sequences of serine protease genes from related species. Nucleotide sequence analysis of the gene revealed an open reading frame containing 1,206 bp which encodes for a polypeptide of 401 amino acid residues. The polypeptide composed of a signal peptide (25 amino acid residues), a prosequence (97 amino acid residues), and a mature protein of 279 amino acid residues. Amino acid sequence comparison revealed that it shared high homology with those of other serine proteases from a number of Bacillus spp. The recombinant F1 protease was efficiently excreted into culture medium using E.coli XL1-Blue harbouring two vectors: pTrcHis bearing the protease gene and pJL3 containing the bacteriocin-release-protein (BRP). Both vectors contain the E.coli lac promoter-operator system. In the presence of 40 uM isopropyl-β-D thiogalactopyranoside (IPTG), the recombinant F1 protease and the BRP were expressed and the mature F1 protease was released into the culture medium. The enzyme was purified through a one-step heat treatment at 70°C for 3 h, and this method purified the protease to near homogeneity. The purified enzyme showed a pH optimum of 9.0, temperature optimum of 80°C, and was stable at 70°C for 24 h in pH ranges from 8.0 to 10.0. The enzyme exhibited a high degree of thermostability with half-lives of 3.5 h at 85°C, 25 min at 90°C, and was inhibited by the serine protease inhibitor, phenylmethanesulfonyl fluoride (PMSF).